Development of a Professional Coaching Model to Enhance Digital Technology Competency for Primary Teachers: A Mixed-Methods Study - Kotchaphan Wilaphan; Rattama Rattanawongsa (Suranaree Journal of Social Science, 2026)
Background and Objectives: In 21st century education, digital technology integration in education is crucial, but primary teachers often struggle with it. Previous professional development efforts have not significantly transformed teachers' learning management practices. Instructional coaching, a promising approach, has shown encouraging behavioral outcomes but lacks empirical research on its effectiveness in authentic classroom contexts. In this study, we aimed to develop and evaluate a new model—the Digital Integration through Coaching and Technological Pedagogical Content Knowledge (TPACK) Framework (DICT model)—designed to enhance primary teachers’ competency in integrating digital technology through TPACK. Methodology: The study employed a mixed-methods design, with the sample group consisting of 64 primary school teachers from 12 schools in two zones of the Bangkok Education Office, specifically focusing on fourth-grade teachers. The development of the DICT model guildelined the ADDIE model approach. Data collection tools included a form to observe and assess teachers' skills in using educational technology based on the TPACK framework, along with semi-structured interviews to understand the views and experiences of both coaches and primary teachers using the model. The data analysis of quantitative data included t-tests and ANOVA. We analyzed qualitative data from reflections and interviews using thematic analysis. Main Results: The DICT model significantly improved teachers' TPACK competencies and confidence in integrating digital technology. The developed DICT model consisted of five core components (coach team, coachee, TPACK-based framework, digital toolkits, and reflective & follow-up system) and five activity steps: (1) provision of knowledge, (2) collaborative planning, (3) observation, (4) reflection, and (5) follow-up. The DICT model significantly improved teachers' knowledge, skills, and behavior when teachers integrated digital technology into learning activities. The mean score for learning management behavior using digital technology increased significantly in the second coaching session when compared to the first coaching session (p < .05). Level 1 teachers revealed a higher integration of digital technology in their teaching compared to pre-teachers and Level 2 teachers. Thematic analysis of interviews and reflections revealed increased teacher confidence, positive attitudes towards technology, and heightened awareness of technology's function. Discussion: The DICT model is an instructional coaching approach that focuses on continuous observation, reflection, and monitoring of teacher action and outcomes. It incorporates group training and personalized feedback, aiming to bridge gaps in technology integration across different subject areas. The model's four-month implementation period allows teachers to adjust to new technologies. The coaching process enhances teachers' confidence in selecting and implementing digital technologies, increasing self-efficacy. It also improves primary teachers' ability to integrate TPACK in practice, transforming technology from an external toolkit to an essential part of instructional design. Conclusions: The DICT model is a sustainable professional development approach for primary teachers to enhance their digital technology competency. It involves continuous observation, reflection, and monitoring, offering group training and personalized feedback. The model enhances primary teachers’ digital integration competency in their classroom activities through coaching and the TPACK framework, while fostering positive attitudes and a better understanding of technology's role in learning design.
Keywords: Digital literacy in education; Educational Leadership and Innovation; Teacher Education and Leadership Studies